Comparison between cytological & histological grading of Breast cancer and its role in prognosis. - Dr. Amita Chavda (BJ Kines: National Journal of Basic & Applied Sciences, 2017)
Aim: To find out utility of grading breast carcinoma on fine needle aspiration cytology (FNAC) as per the criteria proposed by Robinson and Colleagues and compare it with histological grading based on Nottingham’s modification of Bloom and Richardson system, proposed by Elston and Ellis. Methods: Cytological smears of 24 cases of breast carcinoma diagnosed on fine needle aspiration cytology (FNAC), and later on confirmed on histopathology, were graded according to the Robinson grading system. The histological grade as per Nottingham’s modification of Bloom and Richardson system, proposed by Elston and Ellis was also decided in all 24 cases. The cytological grade was compared with the histological grade to know the concordance rate. Results: Out of 24 cases 9 cases were cytologically grade I, while 15 were grade II. Overall concordance between Cytological grade and histological grade was 79.17%. Conclusion: Cytology grading proposed by Robinson and colleagues can be a useful parameter for preoperative prognostication in cases of carcinoma of breast and selected cases requiring neoadjuvant chemotherapy.